Oral microbiome diversity: The curious case of Corynebacterium sp. isolation. (1st August 2022) - Treerat, Puthayalai; McGuire, Brian; Palmer, Elizabeth; Dahl, Erin M.; Karstens, Lisa; Merritt, Justin; Kreth, Jens
Abstract: Oral microbiome sequencing efforts revealed the presence of hundreds of different microbes. Interindividual differences at strain and species resolution suggest that microbiome diversity could lead to mechanistically distinct gene regulation as well as species‐related differences in phenotypes. Commonly, gene regulation and related phenotypes are studied in a few selected strains of a particular species with conclusions that are mostly generalized. The aim of this study was to isolate several species of Corynebacterium using an established protocol that led to the previous isolation of C. durum . Characterization of C. durum interspecies interactions revealed a specific mechanism for chain elongation in Streptococcus sanguinis that was the result of corynebacterial fatty acid production and secretion. While the protocol was successfully applied to isolate what we presumed to be additional Corynebacterium based on several phenotypic traits that seem to be identical to C. durum, genome sequencing of the newly isolated strains placed them closer to Actinomyces . Both Corynebacterium and Actinomyces are suborders of the Actinobacteridae and related species. Our study suggests to take several comprehensive strategies into consideration when taxonomically identifying closely related microorganisms. Furthermore, it seems to be important to test common core phenotypes in bacterial ecology to understand the behavior of specific groups of microbes, rather than simply relying upon genome sequence homology to establish relationships in the microbiome.